Once upon a time in the West - Leone, Sergio (Paramount Pictures, 1968)
This monumental epic ranks among the five or six all-time Western masterpieces. The picture itself is as big as its' Monument Valley locations: as grand as its' fine, distinguished cast: as tough and bawdy as every kid imagines the Old West. Claudia Cardinale as the whore turned madonna. Henry Fonda plays the blackest character of his long career and he's utterly convincing. He's Frank the ruthless, murderous psychopath who suffers no conscience pangs after annihilating an entire family. Jason Robards is the half-breed falsely accused of the terrible slaughter. Charles Bronson plays The Man, who remembers how his brother was savagely tortured. Brilliantly directed by Sergio Leone, this glorious picture re-established the western's significance to the filmmaker's arts.